Bridal couples lay flowers on the monument at Erevan in commemoration of the genocide on Armenians in Turkey in 1915 - Kruijf, Co de,
Bridal couples lay flowers on the monument at Erevan in commemoration of the genocide on Armenians in Turkey in 1915.